The Role of Circular Economy in Transforming Manufacturing Workplace Towards Net Zero Emissions - Afsa Parveen; Nishu Saini; Seema Rani (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
The manufacturing sector is a primary contributor to global environmental issues, such as waste production, resource depletion, and greenhouse gas (GHG) emissions. As industries face increasing pressure to align with net zero emission targets, one revolutionary approach to tackling these environmental issues is circular economy. Unlike the traditional linear